Flexible Manufacturing Organizations: Implications for Strategy Formulation and Organization Design - Nemetz, Patricia L.; Fry, Louis W. (Academy of Management Review, 1988)
Patricia L. Nemetz, Louis W. Fry, Flexible Manufacturing Organizations: Implications for Strategy Formulation and Organization Design, The Academy of Management Review, Vol. 13, No. 4 (Oct., 1988), pp. 627-638